Partisipasi Mahasiswa Kukerta dalam Kegiatan Sosial Masyarakat di Kelurahan Tungkal V, Kecamatan Seberang Kota, Kabupaten Tanjung Jabung Barat - Jannah, Fathul; Fadhilah, Nur; Iswana , Della; Ashfia, Nurul; Qibthiah, Mariatul; Bayanurrahmah, Najjini; Amini, Ma’ripah; Rosalinda, Kelara; Fitriyani, Ecy; Rizal, M. Saifu; Habibi, Ahmad; Ummah, Amelia Khoirum; Sabina, Sandra; Mala, Mita Pita; Jauhari, Mashun Syafuan; Ramadhan, Andre; Fatimah, Siti; Alzazuli, Sulaiman (khidmatan, 2026)
Community service through the Kuliah Kerja Nyata (KUKERTA) program represents the implementation of the university’s Tri Dharma by emphasizing students’ direct involvement in community social life. This activity is motivated by the importance of student participation in supporting social empowerment and strengthening collaboration between higher education institutions and local communities. The purpose of this program is to describe the forms and impacts of KUKERTA students’ participation in community social activities in Tungkal V Subdistrict, Seberang Kota District, Tanjung Jabung Barat Regency. The activity involved local government officials, community leaders, and residents as partners, with students from various academic programs participating. The implementation method employed a Participatory Action Research (PAR) approach combined with the Asset Based Community Development (ABCD) concept through stages of participatory observation, joint planning, implementation, and evaluation. Activities were conducted in the fields of religious affairs, education, social community services, and public health. The results indicate positive qualitative impacts, including increased religious awareness, social solidarity, and harmonious relationships between students and the community. Quantitatively, there was an increase in community participation in religious activities, educational assistance for children, mutual cooperation programs, and health activities such as elderly exercise. Overall, KUKERTA student participation contributed significantly to community empowerment while serving as an effective contextual learning experience for students.